Complicating Eroticism and the Male Gaze: Feminism and Georges Bataille’s Story of the Eye - Chris Vanderwees (Studies in 20th & 21st Century Literature, 2014)
This article explores the relationship between feminist criticism and Georges Bataille’s Story of the Eye. Much of the critical work on Bataille assimilates his psychosocial theories in Erotism with the manifestation of those theories in his fiction without acknowledging potential contradictions between the two bodies of work. The conflation of important distinctions between representations of sex and death in Story of the Eye and the writings of Erotism forecloses the possibility of reading Bataille’s novel as a critique of gender relations. This article unravels some of the distinctions between Erotism and Story of the Eye in order to complicate the assumption that the novel simply reproduces phallogocentric sexual fantasies of transgression. Drawing from the work of Angela Carter and Laura Mulvey, the author proposes the possibility of reading Story of the Eye as a pornographic critique of gender relations through an analysis of the novel’s displacement and destruction of the male gaze.
Keywords: Georges Bataille; Male Gaze; Story of the Eye; Pornography; Eroticism; Erotism; Feminism; Angela Carter; Susan Sontag; Gaze; Vision; Surrealism; Death; Sex